A Reconsideration of Acute Beryllium Disease - Cummings, Kristin J.; Stefaniak, Aleksandr B.; Virji, M. Abbas; Kreiss, Kathleen (Environmental health perspectives, 2009)
Context: Although chronic beryllium disease (CBD) is clearly an immune-mediated granulomatous reaction to beryllium, acute beryllium disease (ABD) is commonly considered an irritative chemical phenomenon related to high exposures. Given reported new cases of ABD and projected increased demand for beryllium, we aimed to reevaluate the pathophysiologic associations between ABD and CBD using two cases identified from a survey of beryllium production facility workers. Case Presentation: Within weeks after exposure to beryllium fluoride began, two workers had systemic illness characterized by dermal and respiratory symptoms and precipitous declines in pulmonary function. Symptoms and pulmonary function abnormalities improved with cessation of exposure and, in one worker, recurred with repeat exposure. Bronchoalveolar lavage fluid analyses and blood beryllium lymphocyte proliferation tests revealed lymphocytic alveolitis and cellular immune recognition of beryllium. None of the measured air samples exceeded 100 ¼g/m³, and most were < 10 ¼g/m³, lower than usually described. In both cases, lung biopsy about 18 months after acute illness revealed noncaseating granulomas. Years after first exposure, the workers left employment because of CBD. Discussion: Contrary to common understanding, these cases suggest that ABD and CBD represent a continuum of disease, and both involve hypersensitivity reactions to beryllium. Differences in disease presentation and progression are likely influenced by the solubility of the beryllium compound involved. Relevance To Practice: ABD may occur after exposures lower than the high concentrations commonly described. Prudence dictates limitation of further beryllium exposure in both ABD and CBD.